Accessing diverse knowledge for problem solving in the MNC: A network mobilization perspective. (19th June 2018) - Parker, Andrew; Tippmann, Esther; Kratochvil, Renate
Abstract : Research Summary : The fundamental challenge of problem solving is synthesizing diverse knowledge for solution development. This article addresses the trade‐off between knowledge diversity, that is, approaching the most relevant individual to maximize the likelihood that he/she possesses diverse knowledge and the ability to access, that is, recognize and assimilate this knowledge. We examine this trade‐off in relation to managers in subsidiaries of multinational corporations (MNCs) and two types of diverse knowledge—novel knowledge and specialist expertise. We use a network mobilization perspective and arguments on network range within and across organizational boundaries, testing our hypotheses on a dataset of 838 ties from 120 managers leading problem‐solving projects. Our study offers implications for the knowledge‐based view of the MNC as well as the problem‐solving perspective in strategy. Managerial Summary : We examine where managers in subsidiaries of multinational corporations (MNCs) access diverse knowledge to solve nonroutine problems. This is underpinned by a trade‐off. To increase chances that the other person holds diverse knowledge, they may reach far in terms of approaching an individual in a different work context; but such far reach diminishes their ability to integrate this knowledge. We resolve this trade‐off. We find that approaching individuals from an MNC unit in another country location but from the same function increases the likelihood of accessing novel knowledge; whereas accessing specialist expertise is more likely achieved by approaching an MNC colleague from another function located in another country and someone working for an external organization. Overall, we provide insights for problem solvers in organizations.